GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 17293 species occurrences available in GBIF matching the query: Country: Guam. The dataset includes 17293 records from 149 constituent datasets: 1 records from CABI Bioscience Fungus Collection. 5 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Porifera. 4 records from Western Australian Museum provider for OZCAM. 3 records from UCBG TAPIR Provider. 1 records from Herbario Museo de La Salle Bogotá (MLS). 83 records from Paleobiology Database. 33 records from iNaturalist research-grade observations. 1 records from EURISCO, The European Genetic Resources Search Catalogue. 322 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 70 records from Macaulay Library Audio and Video Collection. 43 records from Essig Museum of Entomology. 10 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 91 records from Academy of Natural Sciences OBIS Mollusc Database. 1 records from TTU Mammals Collection. 4 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 28 records from KUBI Ichthyology Collection. 619 records from Bishop Museum Natural Sciences Data. 23 records from Missouri Botanical Garden. 1 records from Field Museum of Natural History (Botany) Bryophyte Collection. 10 records from Collection Aves (bird skins) SMF. 4 records from Museum of Zoology, University of Navarra. 3 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 9 records from CONN. 2 records from UMMZ Birds Collection. 17 records from UF FLMNH Ichthyology. 24 records from Harvard University Herbaria. 1077 records from EOD - eBird Observation Dataset. 10 records from AUM Fishes Collection. 19 records from Crustacea collection of National Museum of Nature and Science. 8 records from Spider Mites Collection of Jean Gutierrez. 35 records from AMNH Herpetology Collections. 4 records from Mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 32 records from UMMZ Herpetology Collection. 1 records from Herbarium Specimens of Bonin and Ryukyu Islands. 1 records from Generic Taxonomic Database System on Mysida and Nematoda. 10 records from TNHC Herpetology Collection. 17 records from Fish collection of National Museum of Nature and Science. 2 records from Sea shell specimens database of Mr. Toru Ueda collection, Shizuoka Prefecture Museum of Natural History. 11 records from Invertebrates (GBIF-SE:SMNH). 1 records from Mammal specimens. 21 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 6 records from Collection Arachnology SMF. 7 records from South Australian Museum Australia provider for OZCAM. 5 records from Akita Prefectural Museum:Hiroki Watanabe Collection of mollusca. 1 records from First Record of Eggplant Mealybug, Coccidohystrix insolita, (Hemiptera: Pseudococcidae), on Guam: Potentially a Major Pest. 8 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Pectinoidea. 5 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Conidae. 21 records from KUBI Herpetology Collection. 1 records from University of Vienna, Institute for Botany - Herbarium WU. 2 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 10 records from PRECIS. 1 records from Japan Collection of Microorganisms, RIKEN BioResource Center. 80 records from Collection Mollusca SMF. 1 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 49 records from Herbarium of The New York Botanical Garden. 4 records from Herps Specimens. 20 records from Royal Botanic Garden Edinburgh Herbarium (E). 1 records from UCM Mammals Collection. 19 records from AMNH Mammal Collections. 6 records from HSU Wildlife Mammals. 3 records from Swiss Psyllid (Hemiptera) Collections - Geneva. 22 records from Queensland Museum provider for OZCAM. 2 records from Natural History Museum, Vienna - Herbarium W. 20 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 80 records from AntWeb. 8 records from Herbarium Berolinense. 1 records from UMZC Zoological Specimens. 1 records from mammals. 26 records from Diveboard - Scuba diving citizen science observations. 1 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 1 records from Recent Invertebrates Specimens. 18 records from RBINS collections. 36 records from invertebratezoology. 25 records from Molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 32 records from Hexacoral Database. 1 records from SysTax - Zoological Collections. 1 records from Birds collection of Yamashina Institute for Ornithology. 140 records from Natural History Museum Rotterdam (NL) - Mollusca collection. 53 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 3 records from Naturalis Biodiversity Center (NL) - Mammalia. 1 records from KUBI Ornithology Collection. 41 records from NSW herbarium collection. 1 records from International Fossil Shell Museum (NL) - Mollusca Collection. 81 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 2 records from Arizona State University Lichen Collection. 159 records from Naturalis Biodiversity Center (NL) - Mollusca. 1 records from Naturalis Biodiversity Center (NL) - Botany Wageningen. 21 records from United States National Plant Germplasm System Collection. 10 records from Collection Aves (spirit preserved) SMF. 4 records from Herp specimens. 2 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 67 records from Geographically tagged INSDC sequences. 3 records from Fungi (S). 1 records from Bishop Museum Data (OBIS distribution) (USOBIS). 56 records from Botany (UPS). 3 records from Algae (S). 5 records from Field Museum of Natural History (Botany) Seed Plant Collection. 20 records from UTA Herpetology. 2 records from Bird specimens. 1 records from Database of Fungal Specimens Maintained at the Selected Japanese Herbaria. 80 records from Australian National Insect Collection. 131 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 326 records from LACM Vertebrate Collection. 2 records from Biologiezentrum Linz. 22 records from Birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 8 records from Collection Cnidaria SMF. 1 records from Mosses (S). 53 records from Australia's Virtual Herbarium. 7666 records from NMNH occurrence DwC-A. 6 records from Northern Territory Museum and Art Gallery provider for OZCAM. 1 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Types. 70 records from Natural History Museum (London) Collection Specimens. 6 records from Cryptogamy collection (PC) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 923 records from MAL. 2 records from HSU Wildlife Birds. 4 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 1 records from Lund Museum of Zoology - Insect collections (MZLU). 7 records from WFVZ Bird Collections. 238 records from herpetology. 9 records from Australian National Herbarium (CANB). 8 records from University of Alberta Entomology Collection (UASM). 3 records from Collection Pisces SMF. 15 records from CAS Invertebrate Zoology (IZ). 20 records from Collection Crustacea SMF. 22 records from The System-wide Information Network for Genetic Resources (SINGER). 2 records from UCM Amphibians and Reptiles. 4 records from Planetary Biodiversity Inventory Eumycetozoan Databank. 5 records from Arizona State University Amphibian and Reptile Collection. 3 records from Field Museum of Natural History (Botany) Lichen Collection. 319 records from Australian Museum provider for OZCAM. 1171 records from CAS Ichthyology (ICH). 3 records from DMNH Birds. 628 records from Museum of Comparative Zoology, Harvard University. 3 records from Naturalis National Natural History Museum (NL) – Crustacea_Decapoda. 10 records from Nationaal Herbarium Nederland. 4 records from Flora of Japan Specimen Database. 58 records from CM Herps Collection. 2 records from UTEP Vertebrates. 21 records from NZFUNGI - Collections of the New Zealand National Fungal Herbarium (PDD). 1 records from UWBM Ornithology Collection. 1 records from Lund Botanical Museum (LD). 68 records from AMNH Bird Collection. 2 records from Bryophyte herbarium, Göttingen (GOET). 4 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 7 records from Herpetology Collection. 1350 records from Fishbase. 137 records from KUBI Ichthyology Tissue Collection. 2 records from Field Museum of Natural History (Zoology) Invertebrate Collection.
Keywords: GBIF; biodiversity; species occurrences